Pathogenesis of the Antiphospholipid Syndrome - Willis, Rohan; Harris, E. Nigel; Pierangeli, Silvia S. (Seminars in Thrombosis and Hemostasis, 2012)
The presence of pathogenic antiphospholipid antibodies (aPL) is the characterizing feature of the antiphospholipid syndrome (APS), mediating the recurrent pregnancy loss and thrombosis typical of the disease, through their action on various antigenic targets. Despite the available knowledge regarding the mechanisms by which aPL induce a procoagulant phenotype in the vasculature and abnormal cellular proliferation and differentiation in placental tissues to cause the typical clinical features, these processes still remain incompletely understood. It is also known that inflammation serves as a necessary link between the observed procoagulant phenotype and actual thrombus development, and is an important mediator of the placental injury in APS patients. Even less well understood are the processes underlying the ontogeny of these pathogenic antibodies. This review seeks to highlight what is known about the mechanisms that contribute to the origin of pathogenic aPL and to the action of these antibodies on target antigens that produce the pathological features of APS. We will also examine the feasibility of classifying patients in clinical phenotypes related to underlying pathophysiological mechanisms, and how this could impact the management of patients with novel “targeted” therapeutic strategies.
Keywords: antiphospholipid antibodies; antiphospholipid syndrome; anticardiolipin antibodies; anti-β2-glycoprotein I antibodies; lupus anticoagulant